Makna ἐν Χριστῷ Menurut Paulus dalam Surat 2 Korintus 5:17 Bagi Orang Percaya - Tami Tami (Institut Agama Kristen Negeri Tarutung, 2022)
Abstract:Phrase “It is in Christ (ἐν Χριστῷ)” appears a great many times in the New Testament especially in the books written by Paul.